Investments, export entry and export intensity in small manufacturing firms - Esaku, Stephen (Journal of Industrial and Business Economics, 2020)
We analyze the effect of investment in physical capital on the firm’s choice to enter the export market and increase export intensity. We specifically examine the hypothesis that firm-level investment facilitates small firms to initiate exporting and increase their export intensity. Using propensity score matching techniques, the results we find are remarkable. First, we find that firm-level investments in physical capital significantly increase the probability of export market entry among small firms. Second, we show that small firms that investment significantly increase the probability of expanding their exports, as observed in the high export intensity. This implies that firm-level investment is a substantial component in the firm’s choice to export and may be another channel through which small firms can access export markets despite the presence of sunk entry costs that act as a barrier to entry. Third, we show that firms that invest above the industry average investment level stand the highest probability of entering the export market and expanding their export sales. Moreover, we also find that exporting experience significantly influences the firm’s choice to invest, probably as a measure of upgrading production technology. At the policy level, we observe that export subsidies should be directed at addressing capacity and technology related constraints as these have hampered export entry and export intensity among small firms.
Keywords: Treatment effects model · Investments · Exports · Firm performance · SMEs